Perceptions of empowerment and power in community development programs : case study of Tanganyika Christian Refugee Service - Ruottinen, Teija (2014)
The purpose of the present case study is to examine the local understandings and experiences of community empowerment, especially in terms of the perceived changes and the evolving power relations triggered by the empowerment intervention, in the context of the Tanzanian NGO Tanganyika Christian Refugee Service. Furthermore, on a more general level, the aim of the study is to look into the possibilities of the empowerment approach to reduce the striking inequalities in the Sub-Saharan African countries, offering them a more sustainable way out of poverty.